Analisis Penerapan Standar Akuntansi Pemerintah Terhadap Aset Tetap Pada Kantor Badan Pengelolaan Keuangan Daerah (BPKD) Kabupaten Aceh Tamiang - Malisa Malisa; Afrah Junita; Iqlima Azhar (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2024)
Fixed assets are tangible assets that have a useful life of more than 12 (twelve) months to be used in government activities or utilized by the general public. This study aims to find out how the application of government accounting standards for fixed assets at the Office of the Regional Financial Management Agency in Aceh Tamiang Regency. The data collection method used is library research and field research. The data analysis use descriptive qualitative. The results showed that the application of government accounting standards for fixed assets at the Aceh Tamiang Regency Regional Financial Management Office did not work in accordance with the statement of Government Accounting Standards Number 07. For the classification of fixed assets, the recognition of fixed assets, measurement/assessment of fixed assets have been categorized according to government accounting standard Number 07. However, the depreciation of fixed assets is not in accordance with the government accounting standard statement number 07.